Early experiences of patellofemoral arthritis symptoms: A qualitative study in Gujarat, India - Heta R. Patel; M. Balaganapathy; Bipin Serasiya (Journal of Family Medicine and Primary Care)
Background: This qualitative study aimed to explore the early experiences of individuals with patellofemoral arthritis in the Indian context. Method: The study was conducted in Gujarat, India, with 14 participants, recruited from regional orthopedic outpatient departments. They were interviewed either in person or online using the Zoom platform, with an expert clinician using a semistructured interview guide in the vernacular language. Results: A scoping review was conducted to find the reported symptoms of the condition, which were identified as anterior knee pain, crepitus, pain while sitting down, walking uphill, and kneeling. Thematic analysis was used to analyze the qualitative data, where four domains of initial symptoms of patellofemoral arthritis were identified: pain, crepitus, stiffness, and difficulty in functional activity. The findings suggest that pain was the primary concern for participants in the Indian context, and initial symptoms are highly affected by individual preferences. Conclusion: Acknowledging initial symptoms and measuring their severity must be taken into consideration to improve the prognosis of the condition.